Guinea-Bissau : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2001)
The statistical data on real GDP by sector, nominal GDP by sector, investment-savings balance, output of main crops, stocks, production, and uses of cashew nuts, industrial and artisanal fishing, electricity and water production, alternative consumer price index, central government operations, revenue and expenditure, civil service employment and developments, and the status of public enterprise reform of Guinea-Bissau are presented in this paper. The data on monetary survey, summary accounts of the central bank, balance of payments, and related economic indices are also presented.